Migrasomes, critical players in intercellular communication - Zhiyong Tan; Chadanfeng Yang; Shi Fu; Junchao Wu; Yinglong Huang; Haihao Li; Chen Gong; Dihao Lv; Jiansong Wang; Mingxia Ding; Haifeng Wang (Cancer Cell International)
Abstract Migrasomes are a newly discovered type of extracellular vesicle (EV) formed during cell migration, playing a pivotal role in intercellular communication. These vesicles are generated by retracting fibers of migrating cells and encapsulate various molecules, such as proteins, lipids, and RNA, allowing the transfer of biochemical signals to neighboring cells. Current evidence suggests that migrasomes are involved in a wide range of physiological processes such as embryogenesis, angiogenesis, immune modulation, and mitochondrial quality control. Moreover, migrasomes are implicated in pathological conditions, including cancer metastasis, cardiovascular diseases, and viral infections. To fully understand their significance, it is critical to first explore the molecular mechanisms underlying their formation and function. Recent studies have shed light on the biogenesis, release, and biological properties of migrasomes, all of which are key to understanding their role in cell-to-cell communication. In this review, we provide an up-to-date summary of migrasome biogenesis, release, characterization, and their biological activities in intercellular communication, while also proposing potential new functions for these vesicles.